Long‐term treatment with romiplostim in patients with chronic immune thrombocytopenia: safety and efficacy. (22nd February 2013) - Kuter, David J.; Bussel, James B.; Newland, Adrian; Baker, Ross I.; Lyons, Roger M.; Wasser, Jeffrey; Viallard, Jean‐Francois; Macik, Gail; Rummel, Mathias; Nie, Kun; Jun, Susie
Summary Romiplostim was effective, safe, and well‐tolerated over 6–12 months of continuous treatment in Phase 3 trials in patients with immune thrombocytopenia (ITP). This report describes up to 5 years of weekly treatment with romiplostim in 292 adult ITP patients in a long‐term, single‐arm, open‐label study. Outcome measures included adverse events (including bleeding, thrombosis, malignancy, and reticulin/fibrosis), platelet response (platelet count >50 × 109 per litre), and the proportion of patients requiring rescue treatments. Treatment–related serious adverse events were infrequent and did not increase with longer treatment. No new classes of adverse events emerged. Thrombotic events occurred in 6·5% of patients and were not associated with platelet count. Median platelet counts of 50–200 × 109 per litre were maintained with stable doses of romiplostim (mean 5–8 μg/kg; generally self‐administered at home) throughout the study. A platelet response was achieved at least once by 95% of patients, with a platelet response maintained by all patients on a median 92% of study visits. There was a low rate of bleeding and infrequent need for rescue treatments. In conclusion, this study demonstrated that romiplostim was safe and well‐tolerated over 614 patient‐years of exposure in ITP patients, and that efficacy was maintained with stable dosing for up to 5 years of continuous treatment.